2019
DOI: 10.3390/su11174628
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Integrated Inventory Routing Problem for Cold Chain Logistics Considering Carbon Footprint and Carbon Regulations

Abstract: This paper studies the optimization of cold chain integrated inventory routing problem while considering carbon emissions. First, the carbon footprint in inventory and transportation process for cold chain logistics is accurately identified and quantified. Secondly, based on the carbon regulations, which are carbon cap, carbon cap and offset, carbon cap and trade, and carbon tax regulations, four green cold chain inventory routing optimization models that minimize the total cost are constructed, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…GhannadPour et al [24] analyzed the effect of carbon tax policy on carbon emissions in the distribution design of the cold chain and proposed a dynamic vehicle-routing problem with fuzzy travel time. In Li et al [25], a simultaneous analysis of inventory control and distribution planning was performed to reduce the carbon emission of cold-chain products.…”
Section: Distribution Design Of Cold-chain Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…GhannadPour et al [24] analyzed the effect of carbon tax policy on carbon emissions in the distribution design of the cold chain and proposed a dynamic vehicle-routing problem with fuzzy travel time. In Li et al [25], a simultaneous analysis of inventory control and distribution planning was performed to reduce the carbon emission of cold-chain products.…”
Section: Distribution Design Of Cold-chain Productsmentioning
confidence: 99%
“…Furthermore, cost has frequently been used as a performance assessment criterion and although different functions of cost have been modelled, the literature lacks in analyzing inspection cost (IC) and its impact on the overall cost solution. [19] 2019 Li et al [25] 2019 Song et al [30] 2020 Yan et al [31] 2020 Qiang et al [32] 2020 Wang et al [33] 2020 Zhao et al [34] 2020 TE = transportation emissions, DE = deterioration emissions, Ho = homogeneous vehicles, He = heterogeneous vehicles, PC = penalty cost, IC = inspection cost.…”
Section: Distribution Design Of Cold-chain Productsmentioning
confidence: 99%
“…Heinold and Meisel [8] addressed a routing problem for freight companies where the CO 2 emission cap must be satisfied for each delivery order in a road and rail transportation intermodal network. Li et al [9] optimized an inventory routing problem for cold chain logistics under the CO 2 emission cap. Jharkharia and Das [10] examined the impact of the CO 2 emission cap in a vehicle routing problem with integrated delivery and pickup operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Detailed information is displayed in Table 6, including of the position and amount of waste. And we set the other parameters of the CCLCVRP model according to the former studies [44,51,52], which are shown in Table 7. CCP is an efficient tool to solve the stochastic problem and credibility level γ in CCP is predetermined representing the probability of path success without overloading and reflecting the dispatcher's risk preference.…”
Section: Experimental Designmentioning
confidence: 99%